2008
DOI: 10.1016/j.amepre.2007.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Schedules

Abstract: (2008) 'Shifting schedules : the health e ects of reorganizing shift work.', American journal of preventive medicine., 34 (5). pp. 427-434. Further information on publisher's website:http://dx.doi.org/10.1016/j.amepre. 2007.12.023 Publisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(40 citation statements)
references
References 37 publications
0
39
0
1
Order By: Relevance
“…(13, p296) Driessen et al (24) concluded on the lack of randomized controlled trials (RCT) on organizational interventions to reduce low back and neck pain. There are few reviews on this topic, and these did not apply a systematic review methodology (13), grouped in their synthesis interventions both with and without an organizational/psychosocial component (eg, workstation adjustments only) (13,24) or were restricted to specific groups of workers (eg, shift workers) (25). It is also useful to review more recent intervention studies published since these previous reviews.…”
Section: Effectiveness Of Work Organization Interventions In Wmsd Prementioning
confidence: 99%
See 1 more Smart Citation
“…(13, p296) Driessen et al (24) concluded on the lack of randomized controlled trials (RCT) on organizational interventions to reduce low back and neck pain. There are few reviews on this topic, and these did not apply a systematic review methodology (13), grouped in their synthesis interventions both with and without an organizational/psychosocial component (eg, workstation adjustments only) (13,24) or were restricted to specific groups of workers (eg, shift workers) (25). It is also useful to review more recent intervention studies published since these previous reviews.…”
Section: Effectiveness Of Work Organization Interventions In Wmsd Prementioning
confidence: 99%
“…Previous reviews looking at work organizational or psychosocial interventions were either not systematic (13), combined in their synthesis interventions both with and without an organizational component (eg, computer workstation adjustments only) (24) or focused on specific groups of workers (25) or body regions (upper limbs) (68). Another strength is the use of an extensive search strategy covering 11 key databases in health sciences, social sciences and occupational health, in both English and French.…”
Section: Strengthsmentioning
confidence: 99%
“…Reviews have summarized the effects of specific intervention types such as caffeine (17), bright light and melatonin (18), and changes in shift schedules (19), however these reviews included laboratory-based studies that were conducted among non-shift workers in simulated night shift environments, and findings may not be generalizable. They also included studies that examined outcomes likely irrelevant to long-term health, such as productivity and absenteeism.…”
mentioning
confidence: 99%
“…Some common effects include sleep complaints, fatigue (6,7), diseases and somatic health problems, e.g. cardiovascular diseases (8).…”
mentioning
confidence: 99%